2019
DOI: 10.2147/ijn.s184396
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and biological characterization of the mixture of poly(lactic-co-glycolic acid)/chitosan/Ag nanoparticles for periodontal tissue engineering

Abstract: ObjectiveThis study aims to produce nanoparticles of chitosan (CS), poly(lactic-co-glycolic acid) (PLGA), and silver and investigate the optimal composite ratio of these three materials for periodontal tissue regeneration.MethodsPLGA nanoparticles (nPLGA), CS nanoparticles (nCS), and silver nanoparticles (nAg) were prepared. The antibacterial properties of single nanoparticles and their effects on the proliferation and mineralization of periodontal membrane cells were investigated. Different ratios of nPLGA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…8,9 Besides, Ag@TiO 2 -NTs with a lower initial concentration (0.14ppm) of Ag + ions also achieved an excellent synergistic antibacterial capacity in combination with antibiotics both in vitro and in vivo. 10 Interestingly, it has recently been reported that the AgNPs-loaded biomaterials with continuing releasing extremely low dose Ag + could enhance cell adhesion, 10 spreading, 11 proliferation, 12 reactive oxygen species (ROS) scavenging, 11 and new bone formation 13 by the unique controlled-release characteristic and topographic feature.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Besides, Ag@TiO 2 -NTs with a lower initial concentration (0.14ppm) of Ag + ions also achieved an excellent synergistic antibacterial capacity in combination with antibiotics both in vitro and in vivo. 10 Interestingly, it has recently been reported that the AgNPs-loaded biomaterials with continuing releasing extremely low dose Ag + could enhance cell adhesion, 10 spreading, 11 proliferation, 12 reactive oxygen species (ROS) scavenging, 11 and new bone formation 13 by the unique controlled-release characteristic and topographic feature.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Zang et al [38], the same test showed more dense and well-organized PDLCs in the chitosan scaffold with hJBMMSCSs than the chitosan/anorganic bovine bone and pure chitosan groups. ARS staining of hPDLCs performed by Xue et al [36] recorded more mineralized nodules on the nPLGA/nCS/nAG complex than in negative control group, showing the that this type of membrane may promote cell mineralization. Human mesenchymal stem cells (MSCs) were cultured by Rammal et al [31] on a bone-mimetic material (B-MM) made from inorganic calcium phosphate combined with CS and hyaluronic acid biopolymers, which acted as a framework for the osteogenic potential of MSCs.…”
Section: Results Of Individual Studiesmentioning
confidence: 92%
“…ALP activity of periodontal ligament cells [21], osteoblasts [34,35], and mesenchymal stem or stromal cells [24] was assessed in four studies (Table 5). Three items analyzed the mineralization level of the newly formed bone with the Masson's trichrome staining method [27,33,38], two assessed it with the ARS staining [31,36] and one with the immunofluorescent staining technique for osteocalcin (OCN) [39] ( Table 6). Twelve of the selected papers performed their experiment in vivo, creating bone defects, which were later covered by CS-based scaffolds: Ge et al [21] created bilateral parietal bone defects (with a diameter of 5 mm) in eighteen eight-week-old rats (weight = 180-220 g), scoring the anesthetized cranial skin, exposing calvaria; parietal cranial 15 mm oval-shaped defects were obtained by Jayash et al [25] using a bone trephine drill.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than 3D scaffolding architectures for bone regeneration, the PLGA biopolymer has been mainly considered and utilized to create nano-/micro-particles to deliver biologics such as growth factors, proteins, drugs, or cells to target tissues [ 78 , 111 , 122 , 123 , 124 , 125 , 126 ]. Moreover, PLGA-based, resorbable barrier membranes have been manufactured for guided bone regeneration (GBR) techniques, which prevent soft tissue infiltration and induce bone formation in defect sites in periodontal tissue engineering [ 118 , 127 , 128 , 129 , 130 ].…”
Section: Synthetic Biopolymers For Periodontal Hard Tissue Regenermentioning
confidence: 99%